Optimizing Hybrid Digital Activation in Anne Klappertaart MSMES - Ute Lies Siti Khadijah; Ratu Nadia; Tisha Maudia Rahma; Eliana Johana Rebecca; Indah Nurulliza; Julystia Cantika Isardini; Rahmat Alifin Valentino; Lusi Romaddyniah Sujana (Peneliti Teknologi Teknik Indonesia, 2022)
The COVID-19 pandemic that has lasted for two years has shaken several important sectors in Indonesia. Not only the health sector, but the economic sector was also significantly affected. SMEs in Indonesia will have the same opinion. One of those affected is MSME Anne Klappertaart. This micro, small and medium enterprise is located in Lippo Karawaci, Tangerang. MSME owners feel the need to increase sales by utilizing digital , namely social media. Therefore, the KKN-PPM team helped optimize the digital activation of social media and e-commerce platforms from MSMEs. The KKN-PPM team also explained the use of content that had been planned and created. This is done so that MSME owners can use the content in the future. The results of this activity are brand guidelines, content templates for Instagram feeds and stories, and Shopee accounts. In addition, our team also provides video tutorials that can be viewed again by MSME owners.